Answer:
m=3
Explanation:
Simplifying
18 = 5m + 3
Reorder the terms:
18 = 3 + 5m
Solving
18 = 3 + 5m
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '-5m' to each side of the equation.
18 + -5m = 3 + 5m + -5m
Combine like terms: 5m + -5m = 0
18 + -5m = 3 + 0
18 + -5m = 3
Add '-18' to each side of the equation.
18 + -18 + -5m = 3 + -18
Combine like terms: 18 + -18 = 0
0 + -5m = 3 + -18
-5m = 3 + -18
Combine like terms: 3 + -18 = -15
-5m = -15
Divide each side by '-5'.
m = 3
Simplifying
m = 3
hope this helps